Histopathological images classification by using decision trees and fractal analysis - Türko?lu, Ibrahim; Toraman, Suat (My University, 2007)
In this study, a decision support system is designed which helps the physicians and facilitates their works for detection of various diseases from histopathological images. The developed decision support system is based on pattern recognition. The feature extraction stage of the pattern recognition system is realized by using fractal analysis and a decision tree classifier is used for classification stage. The performance of the proposed pattern recognition system is evaluated with the histopathological images which are taken from hepatic patients. The correct classification rate is 92 % for 50 patient's data.
Karar a?açlari ve fraktal anali?z kullanarak hi?stopatoloji?k i?mgeleri?n siniflandirilmasi
Keywords: Decision trees; Expert system; Fractal analysis; Histopathology; Pattern recognition